Liver transplantation as a definitive treatment for familial hypercholesterolemia: A series of 36 cases. (September 2015) - Mansoorian, Mohsenreza; Kazemi, Kourosh; Nikeghbalian, Saman; Shamsaeefar, Alireza; Mokhtari, Maral; Dehghani, Seyed Mohsen; Bahador, Ali; Salahi, Heshmatollah; Amoozgar, Hamid; Malek Hosseini, Seyed Ali
Abstract FH is a genetic disorder characterized by an increase in serum LDL and total cholesterol values. The afflicted patients are at increased risk of premature atherosclerosis and myocardial infarction. Different treatment modalities are present, including pharmacological agents and surgical procedures. The most effective method of therapy in refractive cases is liver transplantation. Herein, we report our experience on 36 cases of patients with FH undergoing liver transplantation in our center, the main referral center of liver transplantation in Iran. The clinical findings, hospital courses, post‐operative complications, and patient follow‐up are also described.